Understanding Users Attitude to Social Endorsement Advertising of Embarrassing Product - Wang, Chih-Chien; Yang, Yolande; Chiang, Meng (International Journal for Applied Information Management, 2021)
Users on social media have increased rapidly in recent years, social media advertising has become a popular marketing tool for companies to promote their products. A feature of social media advertising is that marketers can use customers' online behavior to create customized advertisements, which are also known as targeting ads. In this study, we conducted experimental testing 2 (advertising type) X2 (product type) to see if increased knowledge of social advertising would influence users' attitudes towards ads. We separated two different types of advertising on Facebook, namely remarketing and social support, and two different types of products, which advertised general products and ads about embarrassing products. The results of this study are that the increase in advertising knowledge is able to (1) affect the perceived value of advertisements from different types of products and (2) different types of advertisements do not affect user attitudes towards advertisements. For future research, we recommend focusing primarily on the demographic and environmental variables of digital advertising users about embarrassing products.